Core/clad phosphate glass fibres containing iron and/or titanium - Ahmed, Ifty; Shahruddin, Sharifah; Sharmin, Nusrat; Furniss, David; Rudd, Chris D. (De Gruyter Open, 2015)
Phosphate glasses are novel amorphous biomaterials due to their fully resorbable characteristics, with controllable degradation profiles. In this study, phosphate glasses containing titanium and/or iron were identified to exhibit sufficiently matched thermal properties (glass transition temperature, thermal expansion coefficient and viscosity) which enabled successful co-extrusion of glass billets to form a core/clad preform. The cladding composition for the core/clad preforms were also reversed. Fe clad and Ti clad fibres were successfully drawn with an average diameter of between 30~50 μm. The average cladding annular thickness was estimated to be less than 2 μm. Annealed core/clad fibres were degraded in PBS for a period of 27 days. The strength of the Fe clad fibres appeared to increase from 303 ± 73 MPa to 386 ± 45 MPa after nearly 2 weeks in the dissolution medium (phosphate buffered solution) before decreasing by day 27. The strength of the Ti clad fibres revealed an increase from 236 ± 53 MPa to 295 ± 61 MPa when compared at week 3. The tensile modulus measured for both core/clad fibres ranged between 51 GPa to 60 GPa. During the dissolution study, Fe clad fibres showed a peeling mechanism compared to the Ti clad fibres.